(untitled) (Research, Society and Development, 2022)
Whey from cheese production is considered a polluter of water bodies and soil when discarded directly into them without prior treatment and is usually present in high volumes in the effluents of cheese industries. Despite this, whey has been shown to be a co-product of significant value for the food industry, since it can be added to various products, increasing their nutritional composition and minimizing the waste of this raw material, in addition to reducing environmental impacts. Through these facts, the main objective of this research was to collect data regarding the destination of whey in dairy products located in the city of Barbacena or microregion. For the collection of such data, a structured online questionnaire with 11 questions was applied to the research participants who are responsible for cheese-producing industries and registered in the Inspection Services SIF, SIE or SIM. Data were computed and tabulated using Excel software. In the industries studied, 55.6% have an Effluent Treatment Station on their premises; the most common destination of whey is animal feed and the predominant cheeses generate sweet whey. With the research, it is concluded that the final destination of whey in the analyzed industries is done properly and consciously, and it is still important to disseminate information relevant to the best alternatives for the use of whey and the use of appropriate technologies in the industries to be able to use the whey more profitably.